Detecting Financial Distress in the Technology Industry: The Moderating Role of Managerial Ownership - Pangaribuan, Meiko Andreas; Siregar, Fachrul A; Muda, Iskandar; Abdullah, Noor Marini Haji (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
This study investigates the influence of internal financial factors profitability and leverage on the likelihood of financial distress in technology companies listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. Using a quantitative approach with 102 data observations, the study also examines the moderating role of managerial ownership in these relationships. Results show that profitability has a significant negative effect on financial distress, indicating that higher profitability lowers the risk of financial trouble. Conversely, leverage has a significant positive effect, suggesting that greater debt levels increase the probability of financial distress. Furthermore, managerial ownership strengthens both the negative relationship between profitability and financial distress and the positive relationship between leverage and financial distress. These findings highlight the importance of sound financial management and corporate governance mechanisms in improving the financial stability of technology firms operating in high-risk, innovation-driven environments.